The Attitude toward Bereavement in Everyday Life in the Jewish Agricultural Settlements of Eretz Israel, from the First Aliyah to the 1920s - Yossi Goldstein; Devorah Giladi (Quest. Issues in Contemporary Jewish History, 2017)
This article explores attitudes toward death and bereavement in the Jewish agricultural settlements of Eretz Israel (Land of Israel) from the First Aliyah (1881) to the 1920s, based primarily on newspapers of the period. The sources indicate that whereas members of the First Aliyah viewed death as a failure of the Zionist act and strived to conceal it to the best of their ability, the pioneers of the Second Aliyah effected a revolution in this realm, articulating a perspective that viewed death in the name of the Zionist act with pride and veneration as an attribute of the “new Jew.” This positive attitude focused on the casualties of Jewish guarding who were killed during clashes with Arabs, but also went further. Overall, the Zionist pioneers perceived blood as a means of actualizing the relationship between the Jew and Eretz Israel and expressed a desire to saturate the Land with their blood. The height of this process was the well-known pre-death utterance of Yosef Trumpeldor – a defender of the Jewish settlements in the Upper Galilee in the 1920s – that “it is good to die for our homeland.” This positive attitude toward sacrifice remained a prominent attribute of Zionism for many years to come.